Efecto citotóxico del extracto etanólico de hojas de annona cherimola en una línea celular de cáncer de colon humano en medio de cultivo con pH ácido - Valarezo Blacio, Gianella Liseth (2015)
Cancer is a group of diseases characterized by the uncontrolled growth of cells with local invasion of tissues and systemic metastasis. Colon cancer is a disease in which malignant cells are located in the intermediate and longer of the intestine portion. Several in vitro studies on the effects of the Annona Cherimola, better known as the custard apple where it has been reported that this plant has various natural compounds of biological interest such as alkaloids and acetogenins have been. Compounds isolated from the Annona cherimola which have shown cytotoxicity against various human tumor cell lines. The implementation of this research project will be held in order to determine the effect cytotoxic ethanolic extract from the leaves of Annona cherimola in cell lines of colon cancer, this being an investigation of prospective pilot type carried out in the laboratories of biotechnology at the National University of Loja in the period September 2014 to July 2015. It was conducted through the development of analytical techniques of cell viability, cell proliferation procedures, which were developed with the help of the dye trypan blue; These protocols helped us determine a favorable decrease of cancer cells in an 87.3%, However, this trial left open to further research what will help to better clarify the doubts present in all the procedures developed in the same. Key Words: Acetogenins, Annona Cherimola, Colon Cancer.